2022
DOI: 10.1007/s00268-022-06578-x
|View full text |Cite
|
Sign up to set email alerts
|

Is Prophylactic Cervical Drainage Effective in Patients Undergoing McKeown Esophagectomy Reconstructed Through the Retrosternal Route with Two‐Field Lymphadenectomy?

Abstract: Background McKeown esophagectomy with two-field lymphadenectomy is the treatment of choice for oncologic esophagectomy. A cervical drain is placed in cases after modern two-field lymph node dissection (M2FD) to provide information on anastomotic leakage. However, the necessity of prophylactic cervical drainage during surgery remains unknown. This study aimed to clarify the clinical significance of cervical drainage in patients who underwent McKeown esophagectomy with M2FD. Methods A total of 293 patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…It can not only minimize the dead space after the dissection but also offer information about hemorrhage, chyle leak, or anastomotic leakage, and enable clinicians to start treatment rapidly (10). The usual practice of cervical drain is placing a silicone or polyurethane foam drainage tube posterior to the anastomosis (10,11). The size of the drainage tube ranges from 10 to 24 Ch/Fr according to physicians' choices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It can not only minimize the dead space after the dissection but also offer information about hemorrhage, chyle leak, or anastomotic leakage, and enable clinicians to start treatment rapidly (10). The usual practice of cervical drain is placing a silicone or polyurethane foam drainage tube posterior to the anastomosis (10,11). The size of the drainage tube ranges from 10 to 24 Ch/Fr according to physicians' choices.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of drainage fluids is usually lower than 50 ml/24 h since the second postoperative day and the difference in amount between patients with or without leakage is not significant (10). However, if the drainage tube penetrates the anastomotic stoma and goes deep into the stomach, the gastric juice may be drained thus increasing the daily volume of drainage fluids significantly (up to 800 ml in the presented case 1) and turning the clear, hematic, light red, or dark red fluids into yellow-green or brown 3.…”
Section: Drainage Fluids Amounts and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A randomized trial of 40 patients found that the routine use of a neck drain for esophageal anastomosis in the neck was not necessary, 10 but the study size was too small to evaluate the utility of a drain for anastomotic leakage. The authors of a larger study of 293 patients suggested that a prophylactic drain may not be universally mandatory for patients with esophageal cancer undergoing McKeown esophagectomy reconstructed through the retrosternal route with two-eld lymphadenectomy, 11 but the study was retrospective in nature.…”
Section: Introductionmentioning
confidence: 99%